Kajian Perbandingan Pendidikan Guru dan Dosen Indonesia dan Amerika Serikat: Comparative Study of Indonesian and US Teacher and Lecturer Education - Dalimunthe, Latifa Annum (Anterior Jurnal, 2013)
The results of the study show that Indonesia has the standardization of the qualifications of a minimum teacher with an undergraduate education and the lecturer is a minimum of S2 education. Compared to the United States, almost the same as for teachers, they must have a minimum education of S1, while for lecturers with S3 education. Then the welfare standards in Indonesia the teachers ’and lecturers’ welfare rights are seen in the form of government awards such as professional allowances, functional, special allowances and educator certificates. If the teacher and beginner’s teacher salary is around Rp. 12-18 million per year. When compared with the United States, for novice teachers, salaries between 25,000 - 35,000 per year. If it’s done in rupiah, it is around Rp. 25,000,000 per month. But do not consider it very large, because the necessities of life in the US are quite high, for example, to rent an apartment for about 1,000 per month or equivalent to IDR 10,000,000. The cost of living for the most economical single is 500 per month. When viewed from the number of teachers and lecturers, the number of teachers in Indonesia is actually abundant but still lacking. The ratio of teachers and students in Indonesia is 1:18, meaning that one teacher teaches 18 students. The comparison outperforms the United States, which is 1:20 in ratio. This condition occurs because of the lack of effective distribution of teachers and tends to accumulate in Java.